MENUMBUHKAN SOLIDARITAS DAN LOYALITAS MELALUI PENINGKATAN KEPEDULIAN TERHADAP MASYARAKAT DENGAN BERBAGI NASI - Danang Nugroho; Ayuni Imama; Dwi Eka Supri Lestari; Anggi Febrianti; Emir Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This abstract discusses the importance of ethics and sharing rice in fostering solidarity and loyalty through increasing concern for society. Ethics and sharing are terms that refer to moral principles and behavior that encourage individuals to pay attention to the needs of others. In this case, sharing rice can be a symbol of love and blessings that can strengthen relationships between individuals and increase feelings of loyalty and solidarity in society. Apart from that, sharing rice can also be a way to increase attention to less fortunate groups. This action not only provides material assistance, but also shows empathy and concern for other people's situations. As a result, sharing rice and ethics can be useful for increasing social awareness of relevant social issues. In situations like this, it is important to consider the ethical values ​​and blessings of sharing rice, as well as how this practice can increase solidarity and loyalty in society.